Family Ocythoidae (Cephalopoda: Octopoda) in Peru - Cardoso, Franz (1998)
The family Ocythoidae on the basis of literature and Peruvian material is reviewed. This family has a single genus and species, Ocythoe tuberculata Rafinesque, 1814. It is an epipelagic species and possibly cosmopolitan in warm oceanic waters (subtropical) of the Atlantic, Pacific and Indico Oceans and Mediterranean Sea. Information on the systematics and Biology of the species is presented.